2019
DOI: 10.1186/s12889-019-6657-9
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D deficiency in northern Taiwan: a community-based cohort study

Abstract: BackgroundVitamin D deficiency has become an important public health problem, however few studies have been conducted in subtropical countries, and the predictors of vitamin D deficiency in people with healthy renal function are unclear. The objective of this study was to evaluate the prevalence and factors associated with vitamin D deficiency in northern Taiwan.MethodsThe cross-sectional study was performed between August 2013 and August 2017, and included 3954 participants without chronic kidney disease (CKD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
45
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(61 citation statements)
references
References 31 publications
12
45
4
Order By: Relevance
“…Of interest, we found evidence that higher intelligence and an increased risk of several psychiatric disorders may cause reduced 25OHD concentrations. With respect to intelligence, this would be consistent with previous links between intelligence and years of education leading to working indoors, and subsequent lower concentrations of 25OHD 60,61 . One of our motivations for undertaking this study was to investigate the hypothesis of a causality 16 relationship between 25OHD and psychiatric disorders 62 .…”
Section: Discussionsupporting
confidence: 87%
“…Of interest, we found evidence that higher intelligence and an increased risk of several psychiatric disorders may cause reduced 25OHD concentrations. With respect to intelligence, this would be consistent with previous links between intelligence and years of education leading to working indoors, and subsequent lower concentrations of 25OHD 60,61 . One of our motivations for undertaking this study was to investigate the hypothesis of a causality 16 relationship between 25OHD and psychiatric disorders 62 .…”
Section: Discussionsupporting
confidence: 87%
“…Young women tend to spend more time indoors with their occupation while a traditional house wife in Jaffna and the elderly could have spent more time outdoors. This finding was comparable to some previous studies (19,20) and further a study in Thailand showed young people may use more sunscreen because of cosmetic reasons (19), however this practice was not observed in this study as only two participants ( (24).…”
Section: Resultssupporting
confidence: 91%
“…However, several studies have shown that there is a high prevalence of vitamin D deficiency in many countries around the world [4,5]. Ming-Jse Lee et al reported that 22.4% of the northern Taiwan population had a vitamin D deficiency [6]. Akhtar et al concluded that vitamin D deficiency was highly prevalent among the South Asian population, including that of India, Pakistan, Bangladesh and Sri Lanka [7].…”
Section: Introductionmentioning
confidence: 99%
“…Silvia Giulianil found that approximately 30% of the population had a deficient 25(OH)D concentration in a large Southern European population [8]. Reports on the vitamin D status in Chinese populations come from Hong Kong, Taiwan and northeastern China populations [6,9,10], but there are few studies on the current status of vitamin D in South Chinese individuals, who have a different diet, lifestyle and climate than those of northeastern China populations.…”
Section: Introductionmentioning
confidence: 99%